Photothermal Prussian blue nanoparticles generate potent multi‐targeted tumor‐specific T cells as an adoptive cell therapy - Elizabeth E. Sweeney; Palak Sekhri; Nethaji Muniraj; Jie Chen; Sally Feng; Joshua Terao; Samantha J. Chin; Danielle E. Schmidt; Catherine M. Bollard; Conrad Russell Y. Cruz; Rohan Fernandes (Wiley, 2024)
Abstract Prussian blue nanoparticle‐based photothermal therapy (PBNP‐PTT) is an effective tumor treatment capable of eliciting an antitumor immune response. Motivated by the ability of PBNP‐PTT to potentiate endogenous immune responses, we recently demonstrated that PBNP‐PTT could be used ex vivo to generate tumor‐specific T cells against glioblastoma (GBM) cell lines as an adoptive T cell therapy (ATCT). In this study, we further developed this promising T cell development platform. First, we assessed the phenotype and function of T cells generated using PBNP‐PTT. We observed that PBNP‐PTT facilitated CD8+ T cell expansion from healthy donor PBMCs that secreted IFNγ and TNFα and upregulated CD107a in response to engagement with target U87 cells, suggesting specific antitumor T cell activation and degranulation. Further, CD8+ effector and effector memory T cell populations significantly expanded after co‐culture with U87 cells, consistent with tumor‐specific effector responses. In orthotopically implanted U87 GBM tumors in vivo, PBNP‐PTT‐derived T cells effectively reduced U87 tumor growth and generated long‐term survival in >80% of tumor‐bearing mice by Day 100, compared to 0% of mice treated with PBS, non‐specific T cells, or T cells expanded from lysed U87 cells, demonstrating an enhanced antitumor efficacy of this ATCT platform. Finally, we tested the generalizability of our approach by generating T cells targeting medulloblastoma (D556), breast cancer (MDA‐MB‐231), neuroblastoma (SH‐SY5Y), and acute monocytic leukemia (THP‐1) cell lines. The resulting T cells secreted IFNγ and exerted increased tumor‐specific cytolytic function relative to controls, demonstrating the versatility of PBNP‐PTT in generating tumor‐specific T cells for ATCT.